Reasons for cancellation of operation on the day of intended surgery in a multidisciplinary 500 bedded hospital - Rajender Kumar; Ritika Gandhi (Wolters Kluwer Medknow Publications, 2012)
Background: Cancellation of operations in hospitals is a significant problem with far reaching consequences. This study was planned to evaluate reasons for cancellation of elective surgical operation on the day of surgery in a 500 bedded Government hospital. Materials and Methods: The medical records of all the patients, from December 2009 to November 2010, who had their operations cancelled on the day of surgery in all surgical units of the hospital, were audited prospectively. The number of operation cancelled and reasons for cancellation were documented. Results: 7272 patients were scheduled for elective surgical procedures during study period; 1286 (17.6 %) of these were cancelled on the day of surgery. The highest number of cancellation occurred in the discipline of general surgery (7.1%) and the least (0.35%) occurred in Ear-Nose-Throat surgery. The most common cause of cancellation was the lack of availability of theater time 809 (63%) and patients not turning up 244 (19%) patients. 149 cancellations (11.6%) were because of medical reasons; 16 (1.2%) were cancelled by the surgeon due to a change in the surgical plan; 28 (2.1%) were cancelled as patients were not ready for surgery; and 40 (3.1%) were cancelled due to equipment failure.]. Conclusion: Most causes of cancellations of operations are preventable.